Interactive Learning Media Based on Sparcol Video Scribe Theme Care About Living Things - Ni Luh Ade Junia Candra Dewi; I Gede Astawan; I Made Suarjana (Universitas Pendidikan Ganesha, 2021)
The lack of availability of learning media that can meet the needs of learning materials can affect the learning process. This study aims to design a prototype and produce an interactive learning media product based on Sparkol Videoscribe on the theme of caring for living things in fourth-grade elementary school, tested for validity. This type of development research uses the ADDIE model (analyze, design, development, implementation, and evaluation). However, the implementation and evaluation stages were not carried out due to the COVID-19 pandemic, and learning was done using an online system. The trial subjects of this development research were two subject content design experts, 2 learning design expert lecturers, 2 media expert lecturers, 1 fourth grade teacher, and 9 students. Meanwhile, the object of this research is the acceptability of the pop-up book media that has been developed. The method used in this research is a questionnaire method by giving assessment sheets to 2 subject content design experts, 2 learning design expert lecturers, 2 media expert lecturers, and 1 fourth grade teacher and 9 students. The data were analyzed using the mean formula to determine the average validity score of the developed media. Based on the results of the analysis of validity tests by experts and teachers, the sparkol video scribe-based learning media on the fifth-grade ecosystem of elementary schools was declared valid with an average score of 3.82 and was suitable for use in learning. Based on the analysis results, the sparkol video scribe-based learning media on the theme of caring for living things in grade IV SD is suitable for use in the learning process.